Caught Between Autonomy and Insecurity: A Work-Psychological View on Resources and Strain of Small Business Owners in Germany - Otto, Kathleen; Baluku, Martin Mabunda; Hünefeld, Lena; Kottwitz, Maria U. (Frontiers in Psychology, 2020)
While research on personality factors and economic success of entrepreneurs has flourished over the years, studies on their specific working conditions and their impact on health and career are surprisingly scarce. This study used a qualitative approach to comprehensively mirror the working situation of German small business owners. To reflect the broadness of this employment type and avoid sampling bias, we applied a quota sampling strategy based on a preliminary typology of solo self-employed respondents we derived from a large quantitative survey. We investigated 29 small business owners who reported, for example, on health complaints, recovery opportunities, and obstacles and resources while running their businesses. Thematic analysis was employed to develop a specific frame model for small business owners based on established work-related stress theories which allowed us to derive concrete hypotheses for further quantitative research. The main results emphasized the meaning of active actions and the workers’ own responsibility for creating working conditions and enabling autonomy. Besides personal preferences regarding the chosen career path, marketability, flexibility, and social networks played a role and explained health and career issues. When it came to practical implications, voluntariness played an essential role for selecting this specific career path. Those being pushed into self-employment as their only viable job opportunity should receive particular support through career counseling to sustain their health.